EFFICACY of Moringa oleifera LEAF MEAL ON THE GROWTH PERFORMANCE OF Clarias gariepinus (AFRICAN CATFISH) - ASIATA ADEKILEKUN, KOLAWOLE; ENOS BARAYA, EDITH; AZEEZAT ADENIKE, JUNAID; ABDUR-RAHMAN KOLAWOLE, MUSTAPHA; QUAZIM OLAWALE, JUNAID (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Partial replacement of fish meal by Moringa leaf meal was conducted in 56 days at the Biological garden of Federal University of Kashere. Four diets(40% crude protein ) including the control (Diet A), Diet B, Diet C and Diet D with an inclusion level of 0%, 10%, 20% and 30% respectively based on fish meal were formulated and tested on Clarias gariepinus. These diets were tested on duplicates of 10 fishes of initial weight of 2.4g±0.07 per bowl. The result obtained showed that there is no significant difference (p>0.05) in final weight gain of fishes fed the control diet (Diet A) and 30% replacement (Diet D). But there was significant difference in control diet and diet B and C. The highest mean weight gain 6.07±0.28g was recorded in fishes fed the control diet while the lowest 2.28±0.21g was recorded in 10% inclusion level. The highest final mean length 10.00±0.12 cm was obtained from fishes fed the control diet while the lowest 8.09±0.20cm was obtained from fishes fed 10% inclusion level. The carcass composition was recorded with the highest protein value of 48.31% recorded in Diet D and the lowest 32.28% in Diet A. This study showed that Moringa oleifera leaves can replace 30% of the fish meal component for African catfish without any adverse effects on growth. However, more study should be done in finding methods for inactivating the antinutritional factors for inclusion of Moringa leaves in the diet of African catfish at higher levels.